Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jpor.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A review of improved fixation methods for dental implants. Part II: Biomechanical integrity at bone–implant interface

Abstract: The understanding of complex mechanical bone behavior and size-dependent properties ranging from a nano- to a macroscopic level are essential in the biomechanical optimization of implants. The requirements of regenerated tissue at the interface include high strength, fracture toughness related to ductility, and time-dependent energy dissipation and/or elastic-plastic stress distribution. Moreover, a strong relationship between strain signals and peri-implant tissue turnover could be expected, so that ideal imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 100 publications
0
31
0
5
Order By: Relevance
“…Young's modulus is often assumed to be 1370 MPa for normal cancellous bone and 13 700 MPa for cortical bone of the mandible, 32 so these values were used to simulate high-density cancellous and cortical bone, respectively. To simulate low-density cancellous bone, Young's modulus was assumed to be 259 MPa based on preoperative patient data.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Young's modulus is often assumed to be 1370 MPa for normal cancellous bone and 13 700 MPa for cortical bone of the mandible, 32 so these values were used to simulate high-density cancellous and cortical bone, respectively. To simulate low-density cancellous bone, Young's modulus was assumed to be 259 MPa based on preoperative patient data.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…1 A number of nanomaterials have been produced to induce various biological functions in vivo. 2,3 However, the majority of the work only focuses on the biological effects of nanomaterials while their intrinsic immunomodulatory effects are often neglected. [4][5][6] Take the bone implant materials: for example, titanium (Ti) metal is extensively used in clinical practice due to its outstanding osseointegration ability.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches have involved improving the interface between the implant and the peri-implant bone tissue. Implant materials and/or implant surface treatments have been developed to augment cell adhesion and protein adsorption at the implant-bone tissue interface [10,11]. Ogawa [12] reported that titanium surfaces treated with ultraviolet light developed a unique electrostatic status and acted as direct cell attractants to effectively reduce the osseointegration period without the aid of ionic or organic bridges, which is a novel physicochemical characteristic of titanium [13].…”
Section: Introductionmentioning
confidence: 99%